Assessment of Air Pollution Tolerance and Physicochemical Alterations of Alstonia scholaris (L.) R.Br. along Roadsides of Lahore, Pakistan - Zahid Mehmood; Ali Hasnain; Muhammad Luqman; Sohaib Muhammad; Narayan Babu Dhital; Arooba John; Maryam Iqbal; Amna Ejaz; Matiba Tufail; Harma; Hsi-Hsien Yang; Muhammad Umer Farooq Awan (Aerosol and Air Quality Research)
Abstract Air pollution has become a severe urban environmental and health problem in several countries around the globe. Air pollutants also affect the physiological, morphological and biochemical processes in plants such as stomatal function, photosynthesis, respiration, leaf area, chlorophyll content, amino acid, pH and plant growth. Lahore is the second largest city in Pakistan facing tremendous stress of vehicle emission. This study evaluated the air pollution tolerance potential of Alstonia scholaris growing along the busiest roads of Lahore city using air pollution tolerance level and physicochemical alterations. Leaf area, ascorbic acid content (AAC), total chlorophyll (TCh) content, leaf extract pH, relative water content (RWC), and dust accumulation on leaf surface were measured for the roadside plantation and compared with the control plants (at background sites, 20 km away from polluted sites). Average value of AAC, TCh content, leaf extract pH, and RWC of A. scholaris in the roadside plantation were, 0.0380 mg g−1, 0.0537 mg g−1, 5.94 and 68.3%, respectively. The average value of dust accumulation on the leaf surface 0.381 mg mm−2 and leaf area 1482 mm2 were higher in roadside than control site. APTI value (0.221) observed for A. scholaris in the roadside plantation was significantly higher than that at the control site (0.165). It is concluded that the air pollution tolerance ability of A. scholaris was higher along the polluted roads of Lahore than in the background control site. Leaf area, AAC, TCh and APTI decrease as traffic flows increase, indicating that the health of A. scholaris was affected by traffic flow.